Determination of Some Biochemical Parameters Changes in Gammarus pulex Exposed to Cadmium at Different Temperature and Different Concentration - Serdar, Osman; Aydın, Rahmı; Calta, Metin (My University, 2021)
In this study, the oxidative stress effects of cadmium (Cd) toxicity depending onwater temperature were investigated on Gammarus pulex. The test organismindividuals were exposed to sublethal concentrations for 96 hours at certain rates(C1; 1/10, C2; 1/20 and C3; 1/40) of LC50 values of Cd for each temperature(10, 14, 18 °C). Malondialdehyde (MDA) level, glutathione peroxidase (GPx),and catalase (CAT) enzyme activities were investigated at the temperaturesdetermined in G. pulex exposed to Cd. With the increasing temperature, the MDAlevel and CAT enzyme activity increased while GPx enzyme activities decreased.The results of this study revealed that the biochemical response caused by Cd onG. pulex had statistically significant differences (p<0.05) with temperature. In thisstudy, the use of MDA levels with CAT and GPx-related enzymes, Cd exposure,toxicity, and temperature change as biomarkers for risk assessment may be useful.
Keywords: Gammarus pulex; glutathione peroxidase; cadmium; malondialdehyde; catalase